Padrões filogenéticos de comunidades vegetais em um gradiente altitudinal na Serra do Cipó, Minas Gerais, Brasil - Mattos, Jacqueline Salvi de (2019)
Since the beginning of ecology studies, scientists have been worried in exploring natural communities and how the vary across time and space, looking for patterns to describe. Mountains are often great systems to study these patterns of diversity and how environmental factors can shape them. Phylogenetic diversity, one of the ways of measuring biological diversity, incorporates the evolutionary history of species, and along with other methods of species distributions, can help in the investigation of biogeographic patterns in many scales. In the present study, we used four metrics of phylogenetics diversity and spatial structure (phylogenetic species richness, phylogenetics species variability, specific overrepresentation score and geographic node divergence) and their relationship to environmental filters, along an elevational gradient, to study the influence of niche conservatism and node allopatry. We have studied the vascular plant flora of rocky grasslands in the Cipó Mountains, located in the Espinhaço Range, Southeastern Brazil. We allocated 180 1m² plots in five areas along the altitude gradient (ranging from 800 to 1400 m) and collected all angiosperm species present in those. We also collected soil properties and declivity. The phylogenetic species variability decreased with altitude, whereas richness increased. Therefore, the clustering of species increased towards more elevated areas. Both metrics presented significate relationships with environmental variables such as pH, nitrogen, phosphorus and potassium, confirming that intensity of environmental filters have also increased with altitude. Regarding the other two metrics, we found three allopatric nodes in the phylogeny, which separates: Monocots from Eudicots, Eriocaulaceae from Poaceae, Xyridaceae from Cyperaceae. With that we could reveal the nodes with the higher degrees of environmental and geographic divergence, which could also lead to exploration of major biogeographical changes in their distributions. Finally, we concluded that there is a pattern of phylogenetic diversity and structure along the environmental gradient of the Cipó Mountains. Thus, plant species from rocky grasslands probably have their main traits conserved, and mostly, are shaped by environmental filters.